Odpowiedzi

2009-12-07T21:28:56+01:00
A)
x+3y=3
x-y=5

x+3y=3
x=5+y

5+y+3y=3
x=5+y

4y+5=3/-5
x=5+y

4y=-2/:4
x=5+y

y=-1/2
x=5-1/2

y=-1/2
x=4,5
c)
3m+n=9
2m-5n=-11

n=9-3m
2m-5(9-3m)=-11

n=9-3m
2m-45+15m=-11/+45

n=9-3m
17m=34/:17

n=9-3m
m=2

n=9-3*2
m=2

n=3
m=2
b)
2x-y=10
x+5y=-17

2x-y=10
x=-17-5y

2(-17-5y)-y=10
x=-17-5y

-34-10y-y=10/+34
x=-17-5y

-11y=44/: (-11)
x=-17-5y

y=4
x=-17-5*4

y=4
x=-17-20

y=4
x=-37

Tu wszędzie przy tych układach mają być oczywiście klamry ;)
Pozdrawiam ;d